OATS TOLERANCE TO BIOTIC STRESSORS AS A BASIS OF ECOLOGIZATION OF PLANT-GROWING - O. A. Zhuikova; G. A. Batalova; T. K. Sheshegova (Зерновое хозяйство России, 2018)
The basis of ecologically safe plant-growing is to supply industry with crop varieties tolerant to biotic stressors. According to phyto sanitary situation in Volga-Vayatka region, cultivation of tolerant varieties is of great importance and can become a solution of the problem. That’s why we studied such new oat varieties of hulled and naked type as ‘Argamak’, ‘Faust’, ‘Dens’, ‘Fakir’, ‘Krechet’, ‘Gunter’, ‘Eklips’, ‘Butsefal’, ‘Vyatsky’ and ‘Persheron’ of North-East RIA selection to evaluate their tolerance to a complex of basic biotic stressors under strong infectious conditions of local pathogens. It was revealed that new varieties were mostly or moderately tolerant to loose smut, crown rust, fusarious root rot and frit fly. Immunity forms to these pathogens were not found among the new varieties, but there was significant difference of their response to the pathogens. The study results showed that hulled and naked varieties of oats didn’t expose any significant difference in the character and degree of damage by crown rust and root rot. It was noticed that naked varieties were more sensitive to loose smut than hulled ones. It was shown that early maturing varieties were the most sensitive to frit fly. Thus, cultivation of new oat varieties of North-East RIA selection allows maintaining ecological balance in eco system through elimination of technogenic contamination and it gives an opportunity to receive safe product for processing industry and fodder for husbandry.